STOCK MARKET INTEGRATION BETWEEN MALAYSIA AND INDONESIA - Christopher Tongku (CALYPTRA, 2014)
This research is done to prove the integration market between Indonesian and Malaysian composite index. In this research, it used the GARCH model because of the classic assumption test of non heteroscedasticity model are not fulfilled. The research is quantitative research. It used the data from yahoo finance starting on January 2008 until December 2012. The samples used in this research are 1220 data from each Indonesian and Malaysian return price in daily basis. The data was processed into several test and hypothesis. The research results indicates that Malaysian composite index have a significant impact on Indonesian composite index in the same day. The data will be useful for investor to predict the return of Indonesian composite index.